THE PROCESS OF LEARNING ISLAMIC RELIGIOUS EDUCATION IN THE PRIVATE MIDDLE SCHOOL OF NAHDLATUL ULAMA MEDAN - Haidir Haidir; Nurmawati Nurmawati; Nailussaid Nasution (Universitas Dharmawangsa Medan, 2020)
The aims of the study were to describe: (1) the learning process activities carried out by Islamic Religious Education teachers, (2) to describe the methods of the Islamic Religious Education learning process, (4) what are the media for the Islamic Religious Education learning process and (4) the evaluation of the Religious Education learning process. Islam at the Nahdlatul Ulama Private Middle School Medan. The research method used is a qualitative method with a phenomenological approach.